Towards Scalable Synthesis of TiSe2 and VSe2 Thin Films - Kadiwala, Kevon; Dipāns, Ēriks; Dipāne, Luīze; Butanovs, Edgars; Polyakov, Boris (Sciendo, 2024)
Transition metal dichalcogenides (TMDs), specifically those involving V and Ti, possess fascinating material properties, making them interesting candidates for scientific studies. The existing growth methods of these materials are typically limited by scalability - either low yield or high cost. Here, we propose an alternative 2-step method valid for scalable production. In the first step, precursor films of Ti / V are deposited using magnetron sputtering, followed by the second step of selenization of these samples using elemental Se in a vacuum-sealed quartz ampoule for conversion to their respective diselenide material. Synthesized films are char-acterised using scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD) and X-ray photoelectron (XPS). The method demonstrated here can be used to increase the active surface area of TiSe2 and VSe2 for their potential catalytic and HER applications using nanostructured substrates, while also providing an opportunity for scalable synthesis of films that can be extended to synthesize other TMDs as well. © 2024 K. Kadiwala et al., published by Sciendo. This is an open-access article Kadiwala, K., et al. "Towards Scalable Synthesis of TiSe2 and VSe2 Thin Films" Latvian Journal of Physics and Technical Sciences, vol. 61, no. 2, Sciendo, 2024, pp. 13-22. https://doi.org/10.2478/lpts-2024-0009 published under the CC BY-NC-ND 4.0 licence.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Magnetron sputtering; thin films; titanium diselenide; transition metal dichalcogenides; vanadium diselenide